Comparative estimation of efficiency of playing method at perfection of technique of fight for the capture of young judoists - Musakhanov A.K; Musakhanov Z.A (Kharkov National Pedagogical University, 2012)
The questions of efficiency of mastering of technique of fight are considered for a capture for young judoists. Directions are selected the use of methods of the strictly regulated exercise and playing methods. In research 28 judoists took part in age 8-10 years. Duration of experiment two weeks. In one group of youths conducted game on snatching out of ribbons (clothes-pins and bandages), fastened on the kimono of opponent. In the second group work of taking of basic captures and educational meetings was conducted on a task on taking of capture. The training program contained playing methods and methods of the strictly regulated exercise. Comparison of the trainings programs defined specificity of their affecting development of different indexes of technique of fight for a capture. Recommended in training on the technique of fight for a capture the combined use of methods of the strictly regulated exercise and playing methods.